2021
DOI: 10.3390/polym13213720
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Optical Device with a Continuous Tunability over 500 nm Spectral Range Using Polymerized Cholesteric Liquid Crystals

Abstract: We report that polymerization makes a robust, practically applicable multifunctional optical device with a continuous wavelength tunable over 500 nm spectral range using UV-polymerizable cholesteric liquid crystals (CLCs). It can be used as a circular polarizer generating an extremely high degree of circularly polarized light with |g| = 1.85~2.00. It can also be used for optical notch filters, bandwidth-variable (from ~28 nm to ~93 nm) bandpass filters, mirrors, and intensity-variable beam splitters. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The PBG position can be adjusted through the pitch and refractive index of NLCs by altering the relative weight ratio of the chiral material to the NLC, [3][4][5] temperature, [6][7][8] or external electric field [9][10][11][12][13] or through photoinduced trans-cis isomerization. [14][15][16] To date, various types of CLC laser devices have been developed, [17,18] and many excellent results have been reported. Jeong et al developed wavelength-tuneable CLC laser array devices capable of continuous wavelength tuning in the full visible spectrum by forming a chiral concentration gradient in dye-doped CLC wedge cells.…”
Section: Doi: 101002/lpor202301256mentioning
confidence: 99%
See 1 more Smart Citation
“…The PBG position can be adjusted through the pitch and refractive index of NLCs by altering the relative weight ratio of the chiral material to the NLC, [3][4][5] temperature, [6][7][8] or external electric field [9][10][11][12][13] or through photoinduced trans-cis isomerization. [14][15][16] To date, various types of CLC laser devices have been developed, [17,18] and many excellent results have been reported. Jeong et al developed wavelength-tuneable CLC laser array devices capable of continuous wavelength tuning in the full visible spectrum by forming a chiral concentration gradient in dye-doped CLC wedge cells.…”
Section: Doi: 101002/lpor202301256mentioning
confidence: 99%
“…To date, various types of CLC laser devices have been developed, [ 17,18 ] and many excellent results have been reported. Jeong et al.…”
Section: Introductionmentioning
confidence: 99%
“…The PBG position can be adjusted through the pitch and refractive index of NLCs by altering the relative weight ratio of the chiral material to the NLC 4,2,5 , temperature [6][7][8] , or external electric field [9][10][11][12][13] or through photoinduced trans-cis isomerization [14][15][16] . To date, various types of CLC laser devices have been developed 17,18 , and many excellent results have been reported. M.-Y.…”
Section: Introductionmentioning
confidence: 99%
“…TSLCs show a good application in optical communication devices, such as wavelength-selective filters, optical attenuators, optical switches, and beam steerers [13][14][15]. The wavelength range of TSLCs can be tuned by doping different concentrations of chiral dopant, forming spatial gradients, designing device structure, applying temperature, or irradiating the material with ultraviolet light [16][17][18][19], which makes them attractive in tunable optical filters [20][21][22][23]. Gao et al reported the development of templated TSLCs and summarized the potential photonic applications, including lasing, optical filters, grating, etc.…”
Section: Introductionmentioning
confidence: 99%